Current understanding of learning psychomotor skills and the impact on teaching laparoscopic surgical skills. (January 2016) - White, Colette; Rodger, Matthew WM; Tang, Thomas
Abstract : Key content: Trainees face many challenges in learning the skill set required to perform laparoscopic surgery. The time spent in the operating room has been detrimentally impacted upon since the implementation of the European Working Time Directive. In order to address the deficit, surgical educators have looked to the benefits enjoyed in the aviation and sports industries in using simulation training. Learning objectives: To summarise the current understanding of the neuropsychological basis of learning a psychomotor skill. To clarify factors that influence the acquisition of these skills. To summarise how this information can be used in teaching and assessment of laparoscopic skills. Ethical issues: The use of virtual reality simulators may be able to form a part of the aptitude assessment in the selection process, in order to identify trainees with the desired attributes to progress into the training programmes. However, as skill improves with practice, is it ethical to exclude novices with poor initial performance assessment before allowing them the opportunities to improve?